2013
DOI: 10.1016/j.poetic.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

How cultural capital, habitus and class influence the responses of older adults to the field of contemporary visual art

Abstract: HighlightsWe explore the responses of 38 older people to contemporary visual art.We interpreted the results using Bourdieu's cultural capital, habitus and field.Those who could not recognise the field created their own meanings.Group dynamics and class mobility helped to determine responses.Participants also used the experience to respond to age associated deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Cohen 2006), which can be linked to work on resilience. Evidence for this comes from the New Dynamics of Ageing programme of research 7 which suggested that the arts can facilitate social connectivity, help address negative societal meta-narratives (Murray et al 2014), and construct socially situated identities that respond to individual and community challenges (Newman, Goulding and Whitehead 2013), providing resources for resilience. Similarly, Young et al (2015) have undertaken a systematic review of the literature on the impact of community-based arts and health interventions on cognition in those with dementia and conclude that such activities have positive effects.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cohen 2006), which can be linked to work on resilience. Evidence for this comes from the New Dynamics of Ageing programme of research 7 which suggested that the arts can facilitate social connectivity, help address negative societal meta-narratives (Murray et al 2014), and construct socially situated identities that respond to individual and community challenges (Newman, Goulding and Whitehead 2013), providing resources for resilience. Similarly, Young et al (2015) have undertaken a systematic review of the literature on the impact of community-based arts and health interventions on cognition in those with dementia and conclude that such activities have positive effects.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Regarding parenting, research has examined individuals' confidence in being a good parent (Dunt et al, 2011), parenting practices, and beliefs concerning child discipline (Lee, 2009). Responses to artwork reflect the perceived value of artwork or an art form (Goulding, 2013;Newman, Goulding, & Whitehead, 2013).…”
Section: Attributesmentioning
confidence: 99%
“…A rubric constitutes everything from behavior to customs and is based on cultivation and is affected by norms: this is (Kamphuis, Jansen, Mackenbach, & van Lenthe, 2015). Other research has defined norms as long-lasting dispositions of the mind and body (Kamphuis et al, 2015;Reese et al, 2012), integrated parts of the person (Newman et al, 2013), or guides to what individuals regard as important in life (Kamphuis et al, 2015;Reese et al, 2012). Regarding daily life, research has examined such norms as young people's healthy eating (Fismen et al, 2012); drinking alcohol (Allan et al, 2012); and orientation about higher education, job opportunities, and careers (Royal, 2012).…”
Section: Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was based upon knowledge that while practice in this area was well established 10 research that demonstrated the success or failure of these activities was limited with few systematically designed studies and little attention given to the role of the art activities themselves (Beard, 2011;Mental Health Foundation, 2011). 11 Although it was acknowledged that there was research using non-positivist social science methods that showed positive impacts of the arts with healthy older people (Newman, Goulding, & Whitehead, 2013).…”
Section: The Reasons For the Use Of Art Activities To Improve The LIVmentioning
confidence: 99%